Disability Representation in Merdeka Curriculum English Textbooks: A Critical Content Analysis - Handiyani Silviana Putri; Sri Wuli Fitriati Fitriati; Yuliati Yuliati (Universitas Pahlawan Tuanku Tambusai, 2026)
The representation of disability in educational materials, particularly textbooks, is an important yet often overlooked aspect of inclusive education. Although Indonesia’s Merdeka Curriculum promotes diversity, the portrayal of individuals with disabilities in English as a Foreign Language (EFL) textbook remains underexplored. This study examines the visibility and social roles of characters with disabilities, focusing on whether they are portrayed as “agents” or “victims” based on the Social Model of Disability. Using Critical Content Analysis, this study analyzed three high school English textbooks (Grades 10–12). The findings indicate that disability is indeed depicted, but inconsistently, with more frequent appearances in Grade 10. All identified characters are portrayed as active, independent, and socially integrated individuals, categorized as “agents. Disability is portrayed positively as independent and capable, but its representation is limited and inconsistent across grade levels.”